The effects of foreign R&D and triadic patent propensity on developing economies efficiency and convergence - Rozilee Asid,; Noor Aini Khalifah, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This research relies on the theory of endogenous growth, where the role of foreign imported capital and triadic patent propensity is assumed to endogenously determine the growth process of a group of 36 developing and emerging economies for the years 1990-2010. Our results confirm the monotonicity hypothesis from both foreign imported technology and triadic patent propensity toward technical efficiency improvement with no indication of pure TFP growth. The results indicate that initial foreign capital and initial triadic patent propensity only minimally improve the technical efficiency change for a small number of economies with nearly halve of the sample deviating from the convergence point.